Developing assistive robots for people with mild cognitive impairment and mild dementia: a qualitative study with older adults and experts in aged care - Law, Mikaela; Sutherland, Craig; Ahn, Ho Seok; MacDonald, Bruce A; Peri, Kathy; Johanson, Deborah L; Vajsakovic, Dina-Sara; Kerse, Ngaire; Broadbent, Elizabeth (BMJ open, 2019)
ObjectivesThis research is part of an international project to design and test a home-based healthcare robot to help older adults with mild cognitive impairment (MCI) or early dementia. The aim was to investigate the perceived usefulness of different daily-care activities for the robot, developed from previous research on needs.DesignQualitative descriptive analysis using semistructured interviews. Two studies were conducted. In the first study, participants watched videos of a prototype robot performing daily-care activities; in the second study, participants interacted with the robot itself.SettingInterviews were conducted at a university and a retirement village.ParticipantsIn study 1, participants were nine experts in aged care and nine older adults living in an aged care facility. In study 2, participants were 10 experts in aged care.ResultsThe themes that emerged included aspects of the robot’s interactions, potential benefits, the appearance, actions and humanness of the robot, ways to improve its functionality and technical issues. Overall, the activities were perceived as useful, especially the reminders and safety checks, with possible benefits of companionship, reassurance and reduced caregiver burden. Suggestions included personalising the robot to each individual, simplifying the language and adding more activities. Technical issues still need to be fixed.ConclusionThis study adds to knowledge about healthcare robots for people with MCI by developing and testing a new robot with daily-care activities including safety checks. The robot was seen to be potentially useful but needs to be tested with people with MCI.